Biodiversity and Distribution Rice Arthropods in Malang Indonesia - Istiqomah, Rina Nur; Tarno, Hagus; Mudjiono, Gatot (Research Journal of Life Science, 2023)
Climate change is closely related to changes in abiotic conditions. These changes could have an impact on agricultural cultivation and affect the existence of agricultural arthropods. Different environmental conditions will influence the distribution patterns, richness and diversity of arthropods living in cultivated land. The research was conducted at 8 rice cultivation locations in Greater Malang. Observation of arthropods using pitfall and yellow pan traps, with a diagonal pattern. The total arthropods obtained were 3,937 individuals, 39 families, 46 genera and 48 species. The highest predator species found were Micraspis discolor, the herbivore Nilaparvata lugens, other insect is Culista incidens, and the predator is Drynus baegamensis. The highest index analysis for diversity in Lowokwaru H'= 3,075 in the high category, evenness in Karangploso E=0,864 in the high category and dominance in Pagelaran D=0,179 in the low category. PCA analysis of species composition divided into 2 habitat types, lowland and medium land groups. Species richness increased with increasing observation locations. Environmental factors will bring in species that are suitable for the habitat. Further research needs to be carried out regarding ecological variables or environmental factors, which affect the patterns composition and species richness of arthropods.